2016
DOI: 10.1007/s00264-016-3153-z
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive versus open transforaminal lumbar fusion: a systematic review of complications

Abstract: Purpose The aim of this study is to compare mTLIF vs. oTLIF with regard to peri-operative complications, operative time, estimated blood loss, fluoroscopic time, and the length of hospital stay. Methods The PubMed and EMBASE databases were searched for relevant articles reporting patients undergoing TLIF, and a comparison between mTILF and oTLIF was performed. The database included patient demographic information, complications, operative time, fluoroscopic time, and the length of hospital stay. Results Fourte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 23 publications
1
36
0
1
Order By: Relevance
“…58,60 Compared with open procedures, minimally invasive spine surgery allows to be addressed through smaller incisions with less soft-tissue damage and postoperative pain, which may lead to shorter hospitalizations and earlier mobility for the patient. 61 MISS techniques may be an excellent solution in the politrauma patients, providing ''damage-control spinal stabilization.'' 62 …”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…58,60 Compared with open procedures, minimally invasive spine surgery allows to be addressed through smaller incisions with less soft-tissue damage and postoperative pain, which may lead to shorter hospitalizations and earlier mobility for the patient. 61 MISS techniques may be an excellent solution in the politrauma patients, providing ''damage-control spinal stabilization.'' 62 …”
Section: Minimally Invasive Surgerymentioning
confidence: 99%
“…3 Costs: The direct hospital costs for each study were lower in MIS TLIF than in OPEN TLIF, associated with less blood loss, fewer days in the hospital, and fewer complications. 12 A financial analysis of the total direct hospital costs (blood, imaging, implant, drugs, physical/occupational or speech therapy, hospital stay) were lower in MIS TLIF than in OPEN TLIF, at USD 19,512 versus USD 23,550, respectively. The cost of the implants was similar.…”
Section: Introductionmentioning
confidence: 97%
“…4 5,9,11 Several studies reported inverted results with 161 minutes for MIS TLIF versus 227.4 minutes for OPEN TLIF, however, because of the heterogeneity detected, the difference was not significant. 12 Hospital stay: In most studies, the duration of the hospital stay for patients who underwent MIS TLIF was significantly shorter than OPEN TLIF, 4.7 days for MIS TLIF versus 8 days for OPEN TIF, as well as a difference of 1 day between MIS TLIF and OPEN TLIF, 3 days for MIS TLIF versus 5 days for OPEN TLIF, 6.1 days versus 8.2 days for MIS TLIF versus OPEN TLIF, respectively, and 3.2 days for MIS TLIF versus 6.8 days for OPEN TLIF. 1,2,8,9 A total of 18 studies reported a significant difference with a decrease of 1.3 days between MIS TLIF and OPEN TLIF.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations